Os pilares da geometria euclidiana plana no ensino básico - Siqueira, Renato Machado (2023)
This work presents some of the main concepts of Plane Euclidean Geometry, showing the basic definitions, theorems, as well as the results of this theory. We also present different ways of approaching these concepts in basic education, using tecnological tools (Geogebra), as well as some detailed demonstrations for a better comprehension of the contents. The present work can be used as a complementary material, which can be followed by the teacher throughout basic education with the pedagogical proposal of being applied in the classroom. The objective is to offer the reader a contextualized work, presented details with several illustrations that can be easily followed.